Create Fat Substitute From Soybean Protein Isolate/Konjac Glucomannan: The Impact of the Protein and Polysaccharide Concentrations Formulations - Huang, Lu; Ren, Yuqing; Li, He; Zhang, Qibo; Wang, Yong; Cao, Jinnuo; Liu, Xinqi (Frontiers in Nutrition, 2022)
In this study, soybean protein isolate (SPI) and coconut oil were emulsified and konjac flour was added to prepare the protein/polysaccharide composite emulsion gel, and the SPI/polysaccharide compound fat substitute was obtained by vacuuming. The effects of different protein and konjac flour addition on the gel system of the mixed emulsion were explored. Sensory evaluation experiments showed that the overall acceptability of fat substitutes added with 1% SPI was higher, and the overall acceptability score of fat substitute with SPI of 1% and konjac content of 4% was the highest. With the increase of protein and konjac content, the juiciness of the samples decreased gradually. The increase of konjac content reduced the brightness of compound fat substitutes and the yellowness of compound fat substitute increases significantly with the increase of protein content. The rheological results showed that the storage modulus (G′) of protein/polysaccharide composite emulsion gel increased rapidly at 65 ºC and formed an ordered network structure. The results of frequency scanning showed that the G′ and loss modulus (G″) increased with the increase of protein and konjac content, forming rigid elastic gel matrix, which provided a basis for the preparation of fat substitute. Texture profile analysis (TPA) results showed that the springiness of all samples was similar to the natural fat after 20 minutes of heating. With the increase of protein and konjac content, the hardness of the samples increased gradually. The results of oral tribology showed that the friction coefficients of all samples were very small. The friction behavior of the samples with SPI content of 1% was similar to that of real fat, which could better simulate the swallowing feeling and lubricity of real fat. To sum up, the appearance of solid fat substitutes prepared with SPI and konjac flour is similar to pork fat, and they show ideal functional characteristics in mechanical properties and oral tribology. Among them, the fat substitute with protein content of 1% and konjac content of 4% is the most popular among consumers.